Beyond Depression? A Review of the Optimal Foraging Theory Literature in Zooarchaeology and Archaeobotany - Jones, Emily Lena; Hurley, David A. (Ethnobiology Letters, 2017)
The use of optimal foraging theory in archaeology has been criticized for focusing heavily on “negative” human-environmental interactions, particularly anthropogenic resource depression, in which prey populations are reduced by foragers’ own foraging activities. In addition, some researchers have suggested the focus on resource depression is more common in the zooarchaeological literature than in the archaeobotanical literature, indicating fundamental differences in the ways zooarchaeologists and archaeobotanists approach the archaeological record. In this paper, we assess these critiques through a review of the literature between 1997 and 2017. We find that studies identifying resource depression occur at similar rates in the archaeobotanical and zooarchaeological literature. In addition, while earlier archaeological applications of optimal foraging theory did focus heavily on the identification of resource depression, the literature published between 2013 and 2017 shows a wider variety of approaches.